A bifunctional superconducting cell as flux qubit and neuron - Pashin, Dmitrii S.; Pikunov, Pavel V.; Bastrakova, Marina V.; Schegolev, Andrey E.; Klenov, Nikolay V.; Soloviev, Igor I. (Beilstein Journal of Nanotechnology, 2023)
Josephson digital or analog ancillary circuits are an essential part of a large number of modern quantum processors. The natural candidate for the basis of tuning, coupling, and neromorphic co-processing elements for processors based on flux qubits is the adiabatic (reversible) superconducting logic cell. Using the simplest implementation of such a cell as an example, we have investigated the conditions under which it can optionally operate as an auxiliary qubit while maintaining its “classical” neural functionality. The performance and temperature regime estimates obtained confirm the possibility of practical use of a single-contact inductively shunted interferometer in a quantum mode in adjustment circuits for q-processors.
Keywords: adiabatic logic cell; flux qubit; Josephson junctio; quantum neuron; quantum parametron; superconducting quantum computers; superconducting quantum interferometer